DAMPAK NILAI PERUSAHAAN, UKURAN PERUSAHAAN, DAN PENGUNGKAPAN CORPORATE SOSIAL RESPONSIBILITY TERHADAP MANAJEMEN RISIKO DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Triani Arofah; Umi Pratiwi; Rasyid Mei Mustafa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
The research aims to analyze the effect of firm size, firm value, and Corporate SosialResponsibility (CSR) disclosure on risk management with Good Corporate Governance (GCG) asa moderating variabel. The research population of manufacturing companies was listed on theIndonesia Stock Exchange in 2016-2018 which revealed annual reports and CSR reports.Samples determined by purposive sampling obtained 369 samples. The data analysis tool usesPartial Least Square (PLS). The research findings show that firm size and CSR disclosure have asignificant positive effect on risk management and GCG is able to moderate the interaction ofCSR and GCG disclosure on risk management. The implication of this research can be useful asa consideration for companies in making adequate policies to improve the quality of corporaterisk management in order to minimize risks that threaten the firm.